Ferrier, the unknowable and the origins of idealism - Mander, W (De Gruyter, 2015)
This paper examines James Frederick Ferrier’s idealist argument against the realist agnosticism of William Hamilton, of the Scottish ‘common sense’ school. Particular attention is paid to Ferrier’s restricted definition of ignorance as pertaining only to what could be known, and to his claim that consciousness in itself (sans objects) and objects in themselves (sans awareness) are contradictory or unintelligible notions. The matter commands attention, in the first place, because this once-important debate has become virtually lost from philosophical memory due to the rapid decline in reputation that both philosophers suffered after their deaths. But secondly, it is worth thinking about for the light it sheds on the origins of the British Idealist movement which followed it.